Challenges in Utilizing LMS Tools to Enhance Collaborative Learning in Open and Distance Learning (ODL) Environments - Gunasegaran, Iswaran; Lavania, Marsha; C. Sandaran, Shanti (Semarak International Journal of Current Research in Language and Human Studies, 2025)
This study explores the challenges faced by lecturers on the use of Learning Management Systems (LMS) tools. It focuses on the effective collaboration process among the instructor and learners in Open and Distance Learning (ODL) within higher education settings in the field of language education. Despite the potential of LMS platforms in facilitating collaborative learning, drawbacks have been identified in both study and practice. The study employs a qualitative method, with semi structured interviews with three language lecturers gather insights into the challenges they face. The data was thematically analyzed using Braun and Clarke’s (2006) approach. The findings indicate that the lecturers face several challenges when using LMS tools in the ODL environments. These challenges emerged from technical and pedagogical aspects such as internet issues, lack of student participation, students’ disengagement, and the lecturers own lack of understanding of LMS tools that leads to underutilization of LMS tools, lack of knowledge of LMS tools, and time management issues. This study highlights the importance of digital pedagogical competencies and the integration of LMS tools to enhance collaborative learning in the field of language education within ODL settings.